Strengthening Local Economic Resilience Through Inclusive and Sustainable Tourism: a Case Study of Kubu Gadang Tourism Village - Afrilian, Pepy (Universitas Terbuka, 2025)
The increasing significance of tourism as a driver of local economic development in Indonesia, particularly in rural areas, underscores the need for a comprehensive analysis of its effects on community welfare. This research aims to investigate the impact of inclusive and sustainable tourism on the economic resilience of Kubu Gadang Tourism Village in West Sumatra. Utilizing a qualitative approach, the study gathered data through direct observations and semi-structured interviews with local stakeholders, including residents and tourism operators. The results indicate a remarkable recovery in tourist arrivals, with over 500 visitors recorded in the first quarter of 2025, significantly contributing to local economic growth. The findings also reveal that the number of local women engaged in food and beverage services has increased from 12 to 30 households, highlighting the empowerment of the community through tourism. Additionally, the study emphasizes the necessity of participatory management and collaborative partnerships to sustain tourism development effectively. The primary conclusion drawn from this research is that Kubu Gadang Tourism Village possesses substantial potential to deliver enduring economic, social, and environmental benefits to its residents. It is recommended that future tourism strategies focus on enhancing community involvement and ensuring equitable distribution of resources to foster long-term sustainability and resilience in the local economy.